Unraveling the molecular pathways of DNA-methylation inhibitors: human endogenous retroviruses induce the innate immune response in tumors - Strick, Reiner; Strissel, Pamela; Baylin, Stephen B.; Chiappinelli, Katherine B. (OncoImmunology, 2016)
Loss of DNA methylation can activate endogenous retroviral expression and dsRNA in cancer cells. This leads to induction of toll-like receptor signaling stimulating an antiviral interferon response. Recent findings provide a therapeutic rationale for combining DNA methylation inhibitors with blockage of immune checkpoint proteins to fight cancer.
EVALuna2:33459